PARADIGMATIC POSSIBILITIES OF APPLYING FIELD THEORY - Mansurova, Takhmina (Журнал иностранных языков и лингвистики, 2023)
The article is devoted to the study of the paradigmatic idiosyncrasy of verbs of connectives. Conclusions are provided with numerous examples.